2017
DOI: 10.1186/s12864-016-3469-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure in the Sherpa and neighboring Nepalese populations

Abstract: BackgroundWe set out to describe the fine-scale population structure across the Eastern region of Nepal. To date there is relatively little known about the genetic structure of the Sherpa residing in Nepal and their genetic relationship with the Nepalese. We assembled dense genotype data from a total of 1245 individuals representing Nepal and a variety of different populations resident across the greater Himalayan region including Tibet, China, India, Pakistan, Kazakhstan, Uzbekistan, Tajikistan and Kirghizsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
4
21
0
Order By: Relevance
“…The power of this approach was first illustrated in human data, whereby adaptive regions of the genome may be revealed in as few as 30 individuals (Pickrell et al, 2007). The extent of distinct and shared genetic adaptations and how these factors relate to the distinct suite of physiological traits exhibited within and across populations is an active area of research (Wuren et al, 2014;Jha et al, 2016;Cole et al, 2017).…”
Section: The Power Of Detecting Selection In Human Genomesmentioning
confidence: 99%
“…The power of this approach was first illustrated in human data, whereby adaptive regions of the genome may be revealed in as few as 30 individuals (Pickrell et al, 2007). The extent of distinct and shared genetic adaptations and how these factors relate to the distinct suite of physiological traits exhibited within and across populations is an active area of research (Wuren et al, 2014;Jha et al, 2016;Cole et al, 2017).…”
Section: The Power Of Detecting Selection In Human Genomesmentioning
confidence: 99%
“…Population-genetic studies in worldwide human populations over the past decade have found ROA ranging in size from tens of kb to multiple Mb to be ubiquitous and frequent even in ostensibly outbred populations [ 1 28 ] and to have a non-uniform distribution across the genome [ 7 , 10 , 13 , 18 ] that is correlated with spatially variable genomic properties [ 2 4 , 18 ] creating autozygosity hotspots and coldspots [ 18 ]. ROA of different sizes have different continental patterns both with regards to their total lengths in individual genomes [ 12 , 18 , 22 , 24 , 26 28 ] and in their distribution across the genome [ 18 ] reflecting the distinct forces generating ROA of different lengths. Studies of ROA in the genomes of ancient hominins [ 29 31 ] and early Europeans [ 32 ] have provided unique insights into the mating patterns and effective population sizes of our early forbearers.…”
Section: Introductionmentioning
confidence: 99%
“…The Sherpa share more genetic affinity with these Tibeto-Burman speaking populations than with other Indo-Aryan populations of Nepal. However, the Sherpa are distinct from other Nepalese populations in that the Sherpa have elevated levels of runs of homozygosity (Cole et al, 2017), and illustrate very little or no admixture with Nepalese or South Asian populations (Cole et al, 2017). Thus, the Khumbu Valley Sherpa can be considered from the perspective of population genetics as a “bottlenecked” population recently derived from Tibetans.…”
Section: The Sherpa a Recently Derived Tibetan Populationmentioning
confidence: 96%
“…Analysis of both autosomal data (Lu et al, 2016; Gnecchi-Ruscone et al, 2017) and uniparental mtDNA and Y-chromosome markers (Bhandari et al, 2015) have shown the Sherpa and Tibetans to share relatively recent common ancestry. Tibetans also share recent common ancestry with other Nepalese populations including the Rai, Magar, Tamang, and Gurung (Cole et al, 2017). The Sherpa share more genetic affinity with these Tibeto-Burman speaking populations than with other Indo-Aryan populations of Nepal.…”
Section: The Sherpa a Recently Derived Tibetan Populationmentioning
confidence: 99%